Pengaruh Gaya Belajar terhadap Hasil Belajar IPA Siswa Sekolah Dasar - Halmuniati, Halmuniati; Asmin, La Ode; Zainuddin, Zainuddin; Isa, La; Burhan, Burhan; Ute, Nilawati (Diniyah: Jurnal Pendidikan Dasar, 2024)
This research aims to see the influence of learning styles on science learning outcomes in one of the elementary schools in Kabawo.  This type of research includes quantitative research. The population in this study was all 21 class V students as the samples obtaining by saturated sampling The instrument in this research utilized questionnaire for learning styles and daily test scores for learning outcomes.  The data analysis technique used were descriptive and inferential analysis using simple linear regression. The research results showed that the visual learning style was 42.86%, the auditory learning style was 23.81% and the kinesthetic learning style was 33.33%.  The results of the hypothesis test show a sig value < 0.05, meaning that there is a significant influence of learning style on science learning outcomes with a large influence of 51.6%.Keywords: Eementary school students, learning styles, learning outcomes, natural science learning,